ENDOCRINOPATHIES AFTER PEDIATRIC HSCT: SCREENING RECOMMENDATIONS AND MANAGEMENT - Siviero-Miachon, Adriana Aparecida; Alves-Junior, Paulo Alonso Garcia; Spinola-Castro, Angela Maria; Bordallo, Maria Alice Neves (JOURNAL OF BONE MARROW TRANSPLANTATION AND CELLULAR THERAPY, 2021)
THE BRAZILIAN SOCIETY FOR BLOOD AND MARROW TRANSPLANTATION (SBTMO) PRESENTS THE BRAZILIAN GUIDELINES ON HEMATOPOIETIC STEM CELL TRANSPLANTATION